2022
DOI: 10.1007/s11030-022-10549-8
|View full text |Cite
|
Sign up to set email alerts
|

Enantiopure β-isocyano-boronic esters: synthesis and exploitation in isocyanide-based multicomponent reactions

Abstract: Various boron-containing isocyanides have been efficiently synthesized from the corresponding enantiopure β-substituted β-amino boronic acid pinacol esters, without need for protecting group interconversion, through a two-step, purification-free procedure. They were employed in a variety of isocyanide-based multicomponent reactions, proving to be reliable components for all of them and allowing the efficient synthesis of unprecedented, boron-containing peptidomimetics and heteroatom-rich small molecules, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Based on the computational studies, the β-amido boronic acids reported in Table 1 were synthesized. Relying on our previous experience [18,19], the Ugi multi-component reaction (Ugi-4CR) was chosen as the key step for the synthesis of boron-enriched peptidomimetics. Starting from enantiopure β-amino boronic acid hydrochloride 1 and formaldehyde (fixed amino and carbonyl components, respectively), a series of selected acids and isocyanides were employed in the reaction.…”
Section: Chemistrymentioning
confidence: 99%
“…Based on the computational studies, the β-amido boronic acids reported in Table 1 were synthesized. Relying on our previous experience [18,19], the Ugi multi-component reaction (Ugi-4CR) was chosen as the key step for the synthesis of boron-enriched peptidomimetics. Starting from enantiopure β-amino boronic acid hydrochloride 1 and formaldehyde (fixed amino and carbonyl components, respectively), a series of selected acids and isocyanides were employed in the reaction.…”
Section: Chemistrymentioning
confidence: 99%